3D bioprinted extracellular matrix mimics facilitate directed differentiation of epithelial progenitors for sweat gland regeneration. (1st March 2016) - Huang, Sha; Yao, Bin; Xie, Jiangfan; Fu, Xiaobing
Graphical abstract: Abstract: Sweat glands perform a vital thermoregulatory function in mammals. Like other skin appendages, they originate from epidermal progenitors. However, they have low regenerative potential in response to injury, and whether adult epidermal progenitors could be specified to differentiate to a sweat gland cell lineage remains largely unexplored. We used bioprinting technology to create a functional in vitro cell-laden 3D extracellular matrix mimics (3D-ECM) with composite hydrogels based on gelatin and sodium alginate because of chemical and structural similarity to ECM components. To achieve specific cell differentiation, mouse plantar dermis and epidermal growth factor were synchronously incorporated into the 3D-ECM mimics to create an inductive niche for epidermal progenitor cells obtained from mice. The biological 3D construct could maintain cell viability, thereby facilitating cell spreading and matrix formation. In vitro data by immunofluorescence and gene expression assay of key cell-surface markers demonstrated that the bioprinted 3D-ECM could effectively create a restrictive niche for epidermal progenitors that ensures unilateral differentiation into sweat gland cells. Furthermore, direct delivery of bioprinted 3D-ECM into burned paws of mice resulted in functional restoration of sweat glands. This study represents the rational design to enhance the specific differentiation of epidermal lineages using 3D bioprinting and may have clinical and translational implications in regenerating sweat glands. Statement of Significance: Sweat gland regeneration after injury is of clinical importance but remains largely unsolved because of low regenerative potential and lack of a definite niche. Some studies have shown sweat gland regeneration with gene-based interventions or cell-based induction via embryonic components, but translation to clinic is challenging. The novelty and significance of the work lies in the fact that we design a 3D bioprinted extracellular matrix that provides the spatial inductive cues for enhancing specific differentiation of epidermal lineages to regenerate sweat glands, which is critical for treating deep burns or other wounds. Our studies are encouraging given the overwhelming advantages of our designed 3D bioprinting construct over other cell delivery technology in maintaining high cell proliferation; another interesting finding is that adult tissue components retain a gland lineage-inductive power as embryonic tissue, which can facilitate translation.